2018
DOI: 10.1002/chem.201704638
|View full text |Cite
|
Sign up to set email alerts
|

Generating Electricity from Water through Carbon Nanomaterials

Abstract: Over the past ten years, electricity generation from water in carbon-based materials has aroused increasing interest. Water-induced mechanical-to-electrical conversion has been discovered in carbon nanomaterials, including carbon nanotubes and graphene, through the interaction with flowing water as well as moisture. In this Concept article, we focus on the basic principles of electric energy harvesting from flowing water through carbon nanomaterials, and summarize the material modification and structural desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 33 publications
1
47
0
1
Order By: Relevance
“…Further investigation on the TEMPO‐CNFs aerogels showed that air flow with low RH (e.g., <55%) produced negligible V oc , while the higher RH above 55% could promote the V oc value progressively up to an equilibrium of ≈110 mV at RH ≈99% ( Figure A; Figure S8, Supporting Information). This indicated that water played a vital role in this electricity‐generation process, in analogue to electricity generation of carbon nanomaterials when exposing to moisture diffusion or water evaporation . As the matter of fact, these biological NFs not only had the nanoscale size and large specific surface area, but also had the higher contents of polar groups (e.g., –OH and –COOH) than most of carbon nanomaterials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation on the TEMPO‐CNFs aerogels showed that air flow with low RH (e.g., <55%) produced negligible V oc , while the higher RH above 55% could promote the V oc value progressively up to an equilibrium of ≈110 mV at RH ≈99% ( Figure A; Figure S8, Supporting Information). This indicated that water played a vital role in this electricity‐generation process, in analogue to electricity generation of carbon nanomaterials when exposing to moisture diffusion or water evaporation . As the matter of fact, these biological NFs not only had the nanoscale size and large specific surface area, but also had the higher contents of polar groups (e.g., –OH and –COOH) than most of carbon nanomaterials.…”
Section: Resultsmentioning
confidence: 99%
“…For example, nanofluidic energy devices could mimic ion channels and ion pumps on cell membranes in biological systems, in which specially designed nanochannels converted transmembrane ionic gradients into electrical impulse . Certain nanogenerators based on carbon nanomaterials (e.g., carbon nanotubes (CNTs), graphene, and graphene oxide (GO)) could harvest electric energy from flowing water and moisture, in which specific modification and structural design were required to regulate water behavior on or within carbon nanomaterials . To be noted, so far carbon‐based nanomaterials have mainly been used to produce nanogenerators for electricity harvest from water.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive exploration of functional materials and nanotechnology has advanced traditional energy‐converting technologies including (bio)fuel cells, photovoltaics, piezoelectrics, and thermoelectrics, and has also inspired innovative power‐generating approaches . Recently, electrical potential/current generation arising from solid–liquid or solid–gas interactions has attracted increasing attention both in fundamental research and industrial applications.…”
Section: Power Generation Based On Asymmetric Moisture Diffusionmentioning
confidence: 99%
“…The extensive exploration of functional materials and nanotechnology has advanced traditional energy-converting technologies including (bio)fuel cells, [35] photovoltaics, [36] piezoelectrics, [37] andt hermoelectrics, [38] and has also inspired innovative power-generating approaches. [39] Recently,e lectrical potential/ current generation arising from solid-liquid or solid-gas interactions has attracted increasing attention both in fundamental research and industrial applications. Voltage generation resulting from ionic or nonionic flows on graphene has been reported previously, [40] but the output was limitedt oaf ew millivolts, and was insufficient to support even small-sized devices.G O, rich in hydrophilic oxygen-containing functional groups (e.g., carboxyl and hydroxyl groups) as stated, is one material of great interestf or the preparation of moisture-electric energy transformation (MEET) devices for electricity generation by water adsorption and proton diffusion.Z hao et al described a power-generation phenomenon of a2 .8 mm-thick GO film (GOF) with ap reformed oxygenated group gradient( named as gradientGOF,g-GOF), [41] preparedb yt he moisture/electric field polarization co-induced gradient process (Figure 2a).…”
Section: Power Generation Based On Asymmetric Moisture Diffusionmentioning
confidence: 99%
“…Since the HV phenomenon was discovered with carbon nanotubes (CNTs) in 2003, carbon nanomaterials were extensively investigated and considered as the most promising candidates for HV generators [6]. So far plenty of carbon nanomaterials exhibit HV effect with no need of a pressure gradient, including 0D graphene quantum dots (GQDs), 1D CNTs, 2D graphene or graphene oxide (GO), 3D graphene foam, and so on [7,8]. Yet, unlike photovoltaic effect, research on the HV effect is in its infancy and calls for continued efforts to materialize its great potential.…”
Section: Introductionmentioning
confidence: 99%